Real-time fMRI feedback impacts brain activation, results in auditory hallucinations reduction: Part 1: Superior temporal gyrus -Preliminary evidence-. (April 2020) - Okano, Kana; Bauer, Clemens C.C.; Ghosh, Satrajit S.; Lee, Yoon Ji; Melero, Helena; de los Angeles, Carlo; Nestor, Paul G.; del Re, Elisabetta C.; Northoff, Georg; Whitfield-Gabrieli, Susan; Niznikiewicz, Margaret A.
Highlights: A single session of real-time fMRI neurofeedback significantly reduced activation in the superior temporal gyrus (STG) post neurofeedback. Reduction of activation in STG while ignoring voices reduced the severity of auditory hallucinations (AH) in patients with pharmacology-resistant AH. There was a significant correlation between the reduction in STG activation and the reduction in AH scores post neurofeedback. Abstract: Auditory hallucinations (AH) are one of the core symptoms of schizophrenia (SZ) and constitute a significant source of suffering and disability. One third of SZ patients experience pharmacology-resistant AH, so an alternative/complementary treatment strategy is needed to alleviate this debilitating condition. In this study, real-time functional Magnetic Resonance Imaging neurofeedback (rt-fMRI NFB), a non-invasive technique, was used to teach 10 SZ patients with pharmacology-resistant AH to modulate their brain activity in the superior temporal gyrus (STG), a key area in the neurophysiology of AH. A functional task was designed in order to provide patients with a specific strategy to help them modify their brain activity in the desired direction. Specifically, they received neurofeedback from their own STG and were trained to upregulate it while listening to their own voice recording and downregulate it while ignoring a stranger's voice recording. This guided performance neurofeedback training resulted in a) a significant reduction in STG activation while ignoring a stranger's voice, and b) reductions in AH scores after the neurofeedback session. A single, 21-minute session of rt-fMRI NFB was enough to produce these effects, suggesting that this approach may be an efficient and clinically viable alternative for the treatment of pharmacology-resistant AH.